Adaptive time‐varying formation control of uncertain Euler–Lagrange systems with event‐triggered communication. (2nd September 2021) - Long, Jiang; Wang, Wei; Liu, Kexin; Huang, Jiangshuai
Abstract: This article is concerned with time‐varying formation control of networked Euler–Lagrange systems in the presence of unknown system parameters and event‐triggered communication. Under a directed graph condition, a novel distributed adaptive formation control scheme is proposed. In order to reduce the communication burden among connected agents, a dynamic triggering condition is designed without the need of continuous monitoring of neighboring states. Zeno behavior that may exist in each agent can be rigorously excluded by introducing a dynamic variable into the triggering condition. It is shown that with the proposed control scheme, all the closed‐loop signals are uniformly bounded and all the agents' generalized coordinates can form a time‐varying formation configuration. The effectiveness of the proposed control scheme is validated with simulation results.